Pengelolaan Sistem Informasi Akademik Berbasis SMS Gateway di MTs. Ma’arif 7 Bomo Punung Kabupaten Pacitan - Heri Widiyantoro; Sumardi Sumardi; Sofyan Anif (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2015)
The purposes of this study are: to describe the planning design and the implementation of the system as well as describe the public response to the school. The methods used in this study is a qualitatif approach, that is by interviewing, observing, and documenting as the data collection techniques. The planning of system design, is begun by doing a needs analysis that will be “shared” through SMS access, i.e student’s attendance, the student’s scores, and the notices to the student’s parents. The system implementation is applied to two users groups. They are internal user and external user. From the results of the test of system implementation it is obtained that the timeliness rate is 6.8 seconds, the accuracy of the system is 100 %, and reliability rate is 100%, and the operating procedure is quite easy and familiar. While the public response fully supports the implementation of academic information system, because it can be accessed anytime, and averywhere through SMS, as well as can foster a public positive image to the school, because of the changes and improvements made by the school especially in the academic services as a new breakthrough in the field of technology.